Molecular Surveillance of Artemisinin-Based Combination Therapies Resistance in Plasmodium falciparum Parasites from Bioko Island, Equatorial Guinea - YaQun Liu; XueYan Liang; Jian Li; JiangTao Chen; HuiYing Huang; YuZhong Zheng; JinQuan He; Carlos Salas Ehapo; Urbano Monsuy Eyi; PeiKui Yang; LiYun Lin; WeiZhong Chen; et al. (Microbiology Spectrum, 2022)
ABSTRACT Artemisinin-based combination therapies (ACTs) resistance has emerged and could be diffusing in Africa. As an offshore island on the African continent, the island of Bioko in Equatorial Guinea is considered severely affected and resistant to drug-resistant Plasmodium falciparum malaria. However, the spatial and temporal distribution remain unclear. Molecular monitoring targeting the Pfcrt, Pfk13, Pfpm2, and Pfmdr1 genes was conducted to provide insight into the impact of current antimalarial drug resistance on the island. Furthermore, polymorphic characteristics, haplotype network, and the effect of natural selection of the Pfk13 gene were evaluated. A total of 152 Plasmodium falciparum samples (collected from 2017 to 2019) were analyzed for copy number variation of the Pfpm2 gene and Pfk13, Pfcrt, and Pfmdr1 mutations. Statistical analysis of Pfk13 sequences was performed following different evolutionary models using 96 Bioko sequences and 1322 global sequences. The results showed that the prevalence of Pfk13, Pfcrt, and Pfmdr1 mutations was 73.68%, 78.29%, and 75.66%, respectively. Large proportions of isolates with multiple copies of Pfpm2 were observed (67.86%). In Bioko parasites, the genetic diversity of Pfk13 was low, and purifying selection was suggested by Tajima’s D test (−1.644, P > 0.05) and the dN/dS test (−0.0004438, P > 0.05). The extended haplotype homozygosity analysis revealed that Pfk13_K189T, although most frequent in Africa, has not yet conferred a selective advantage for parasitic survival. The results suggested that the implementation of continuous drug monitoring on Bioko Island is an essential measure. IMPORTANCE Malaria, one of the tropical parasitic diseases with a high transmission rate in Bioko Island, Equatorial Guinea, especially caused by P. falciparum is highly prevalent in this region and is commonly treated locally with ACTs. The declining antimalarial susceptibility of artemisinin-based drugs suggested that resistance to artemisinin and its derivatives is developing in P. falciparum. Copy number variants in Pfpm2 and genetic polymorphisms in Pfk13, Pfcrt, and Pfmdr1 can be used as risk assessment indicators to track the development and spread of drug resistance. This study reported for the first time the molecular surveillance of Pfpm2, Pfcrt, Pfk13, and Pfmdr1 genes in Bioko Island from 2017 to 2019 to assess the possible risk of local drug-resistant P. falciparum.